Islamic character formation in elementary schools: Teachers as role models in Bandura’s social cognitive theory - Tarsono, Tarsono; Hidayat, Agus; Munawaroh, AH Eviyani; Abdurrahman, Ihsan; Koswara, Ujang; Maulana, Hamdan (Jurnal Iman dan Spiritualitas, 2025)
Education is a process of maturing a person, including the method of education that must be considered, especially during the elementary school years, as students tend to imitate. The purpose of this study was to determine the integration of Bandura's theory with the concept of Islamic education. The method employed was a mixed-methods approach (qualitative and quantitative) involving a quasi-experimental design and interviews. The findings revealed a strong convergence between Bandura's social cognitive learning theory and the concept of Islamic moral education. Data from 15 case studies showed that 78% of schools that systematically implemented teacher role modeling experienced significant improvements in student behavior.